The Kohler Family, 1911 - Laval Collection:::::::::
Lottie Pickford Kohler, 55, (Rollin's great aunt) with her husband George Kohler, 57, and their adopted daughter, Olive Ruth, 3. Both Kohler parents were successful entrepreneurs of Fresno's pioneer era who had started their adult lives as wage laborers. Lottie Pickford Kohler (1856-1919) was Fresno's leading female entrepreneur around the turn on the century. She started with rented boarding houses and went on to build Fresno's first apartment complex. She saw that her tenants had nowhere to wash their clothes, so she built the city's first commercial laundry, which grew to serve many hotels and restaurants with a fleet of delivery trucks. Lottie also owned agricultural land, which she leased to farmers and was one third partner in a Sierra Nevada gold mine, named "The Lottie Kohler." In this photo, the Kohlers are seated in their 1908 Columbia Mark LXX Electric Victoria Phaeton automobile. A decade earlier, they had been the first family in Fresno to purchase an electric car, an 1899 Columbia Runabout. In the background are the Kohler Apartments, right, and Kohler Hall (their home), left. The three story Kohler apartment building was the first of its kind in Fresno, built in 1900. The two story home on the left was divided down the center to house two generations of the Pickford Family. Olive Ruth Kohler was the biological daughter of Lottie Matheisen, daughter of Mrs. Kohler's sister, Olive Pickford Matheisen. The father was Matheisen's first husband, Charles Shaw. The marriage appears to have failed early, possibly before Olive Ruth was born. Thus, the baby was adopted and raised by the Kohlers. Rollin Pickford remembered his cousin Olive Ruth as a sickly child. Olive Ruth died in 1922 at age 14, following Lottie Kohler's death in 1919 at age 63.